Reinforcement of an industrial structure with two types of energy dispensers (Gaceta Técnica, 2016)
This paper presents the reinforcement of a flour storage silo affected by the earthquake of April 16, 2016, in ECUADOR, which had a moment magnitude of 7.8. Immediately after the earthquake carbon fiber was placed in the affected elements and the block masonry was changed with light walls in such a way to continue working. A seismic hazard study was carried out and two uniform seismic hazard spectra were determined for 975 and 2475 years of return period. To reinforce this structure it is proposed to place steel diagonals in the subsoil, in such a way that the loads that are generated go directly to the foundation. On the ground floor will be placed Shear Link power dissipators and on the next floor high TADAS heat sinks. The reinforced structure was analyzed for the spectra obtained in Manta from the earthquake of April 16 and for the two earthquakes of uniform seismic hazard indicated.
Keywords: shear Link power dissipators; TADAS power dissipators; seismic reinforcement of an industrial structure; earthquake april 16 Ecuador